Host–microbiome mutualism drives urea carbon salvage and acetogenesis during hibernation - Matthew D. Regan; Edna Chiang; Michael Grahn; Marco Tonelli; Fariba M. Assadi-Porter; Garret Suen; Hannah V. Carey (Proceedings of the National Academy of Sciences, 2026)
Hibernation is a seasonal survival strategy employed by certain mammals that, through torpor use, reduces overall energy expenditure and permits long-term fasting. Although fasting solves the challenge of winter food scarcity, it also removes dietary carbon, a critical biomolecular building block. Here, we demonstrate a process of urea carbon salvage (UCS) in hibernating 13-lined ground squirrels, whereby urea carbon is reclaimed through gut microbial ureolysis and used in reductive acetogenesis to produce acetate, a short-chain fatty acid (SCFA) of major value to the host and its gut microbiota. We find that urea carbon incorporation into acetate is more efficient during hibernation than the summer active season and that while both host and gut microbes oxidize acetate for energy supply throughout the year, the host’s ability to absorb and oxidize acetate is highest during hibernation. Metagenomic analysis of the gut microbiome indicates that genes involved in the degradation of gut mucins, an abundant endogenous nutrient, are retained during hibernation. The hydrogen disposal associated with reductive acetogenesis from urea carbon helps facilitate this mucin degradation by providing a luminal environment that sustains fermentation, thereby generating SCFAs and other metabolites usable by both the host and its gut microbes. Our findings introduce UCS as a mechanism that enables hibernating squirrels and their gut microbes to exploit two key endogenous nutrient sources—urea and mucins—in the resource-limited hibernation season.